Suitability of several naphthalene metabolites for their application in biomonitoring studies - Klotz, Katrin; Zobel, Melanie; Schäferhenrich, Anja; Hebisch, Ralph; Drexler, Hans; Göen, Thomas (Toxicology Letters, 2018)
Naphthalene occurs together with polycyclic aromatic hydrocarbons (PAHs) at industrial workplaces and is ubiquitous in the environment. For biological monitoring of naphthalene exposures, up to now mainly 1- and 2-naphthol in urine have been used. Recently, we proposed 1,2-dihydroxynaphthalene (1,2-DHN) and the 1- and 2-naphthylmercapturic acid (1- and 2-NMA) as new urinary biomarkers to characterise a naphthalene exposure. In this study, in a collective of nine occupationally exposed workers handling with creosote the naphthalene metabolites 1,2-DHN, 1- and 2-NMA as well as 1- and 2-naphthol were analysed in order to evaluate the suitability of the different parameters for their application in biomonitoring studies. Additionally, air sampling was conducted to characterise the exposure in task related exposure situations at different workplaces. In the analysed 51 urine samples, 1,2-DHN was the main metabolite with concentrations ranging from 2.3 to 886 μg/g creatinine (crea) (median 34 μg/g crea). For the sum of 1- and 2-naphthol, concentrations in the range of 2.6-174 μg/g crea (median 15 μg/g crea) were observed. 1-NMA concentrations were in the range of < LOD-2.4 μg/g crea (61% > LOD), while 2-NMA was not detected in the analysed urine samples. The biomarkers 1,2-DHN, 1- and 2-naphthol as well as 1-NMA showed significant correlations, which pointed out to naphthalene as the common exposure source. The poor correlations between naphthalene in the air and the biomarkers in urine may be a result of the varying exposure situations and may indicate not solely inhalative, but additional dermal uptake. 1,2-DHN was the most sensitive and, together with 1-NMA, the most specific parameter of the biological monitoring of naphthalene exposure at workplaces. Further studies with this parameter are needed for individuals at different workplaces as well as for persons of the general population without occupational PAH exposure to characterise 1,2-DHN levels as well as to establish their relationship with the naphthalene exposure.
EVALuna2:35248